Perceptions of environmental pollution and attitudes in university students - Casa, Manuela (2019)
Every human being has perceptions, which is the process of organization and interpretation of sensory impressions in order to give meaning. The environmental perception implies a process of recognizing the environment through the senses, which intervenes the attitudes with respect to the environment, which are favorable or unfavorable feelings that the population has towards the characteristics of the environment. In this way, the objective of the research was to determine perceptions about pollution and environmental attitudes in the students of the pre-degree of the Faculty of Education Sciences of the National University of the Altiplano, Puno. Study that was carried out during the academic year 2013. The methodology  it was non-experimental  with descriptive correlational, with quantitative and qualitative data, 778 students were taken as a population and the sample of the study was made up of 113 students, who have been selected by means of sampling no probabilistic, to whom the environmental pollution perceptions test and a Likert-type attitude scale were applied. The results of this research show a positive influence according to the statistical design of chi square which was 62,534 between the variables of perceptions about environmental pollution and the attitudes of the students. It is concluded that there is a positive relationship between the environmental perception and the environmental attitudes of the students of the pre-degree of the Faculty of Education Sciences, which allows university students to have a high responsibility in changing attitudes towards a sustainable society.